Pengaruh Kebajikan Organisasi Terhadap Perilaku Kewargaan Organisasi Dengan Kebahagiaan Sebagai Variabel Mediasi - Zera Rianjerry; Heru Kristanto (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This research is motivated by the importance of citizenship behavior (Organizational Citizenship Behavior/OCB) in enhancing organizational effectiveness, particularly in higher education institutions. Although organizational virtuousness is believed to foster positive employee behaviors, few studies have examined the mediating role of happiness in this relationship, especially within Indonesian university contexts. This study aims to analyze the effect of organizational virtuousness on OCB with happiness as a mediating variable, focusing on employees at Duta Wacana Christian University and limiting the scope to these variables. The theoretical foundation of this research is based on social exchange theory and positive psychology, emphasizing the significance of virtue and psychological well-being in organizations. This study employs a quantitative approach with a cross-sectional survey method. The research population consists of all permanent employees at Duta Wacana Christian University, with a selected sample of 150 respondents using purposive sampling. Data were collected using standardized questionnaires and analyzed with Structural Equation Modeling (SEM) using Partial Least Square (PLS) with SmartPLS application. The calculation results show that organizational virtuousness has a significant effect on happiness (coefficient = 0.666; p = 0). Happiness also has a significant effect on OCB (coefficient = 0.313; p = 0), and organizational virtuousness also has a direct and significant effect on OCB (coefficient = 0.529; p = 0). Mediation testing using the bootstrap method indicates that happiness partially mediates the relationship between organizational virtuousness and OCB, with an indirect effect of 0.208 (p = 0). These findings highlight the importance of strengthening organizational virtuousness and creating a work environment that supports employee happiness to encourage citizenship behavior in higher education institutions. The analysis results show that organizational virtuousness has a positive and significant effect on OCB, both directly and indirectly through happiness as a partial mediator. Happiness is proven to partially mediate the relationship between organizational virtuousness and OCB. These findings highlight the importance of strengthening organizational virtuousness and creating a work environment that supports employee happiness to encourage citizenship behavior in higher education institutions.